2013
DOI: 10.1111/jse.12047
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of genetic diversity in a small, isolated population of ancient tree Erythrophleum fordii

Abstract: Ancient trees remaining in natural areas from once widespread forest due to overexploitation and habitat modification would naturally regenerate to form small isolated populations after the halting of disturbance. The genetic processes and consequence of this regeneration are generally unknown, which prevents the effective conservation and management of these populations. One such population, an Erythrophleum fordii population, is located in Dinghushan National Nature Reserve (China). Owing to the remarkably h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
2
6
1
Order By: Relevance
“…Such random mating also existed in the well‐preserved population of DH Mountain whose f value was 0.0082 (Table ). This is consistent with our previous data with f values of −0.058 to 0.022 in different age classes in the population of DH Mountain (Zhu et al, ). Since E .…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Such random mating also existed in the well‐preserved population of DH Mountain whose f value was 0.0082 (Table ). This is consistent with our previous data with f values of −0.058 to 0.022 in different age classes in the population of DH Mountain (Zhu et al, ). Since E .…”
Section: Discussionsupporting
confidence: 94%
“…fordii in one well‐preserved population using nine microsatellites in the DH Mountain, a nature reserve. Although our previous study reported higher genetic diversity in the DH Mountain (a H O of 0.606 and H E of 0.586, Zhu et al, ) than all the Feng Shui populations we investigated here, our present study using a new set of microsatellites indicated this was not the case (Table ). In fact, the genetic diversity of the population of DH Mountain was only significantly higher than that of the population of WYG village in A P value (Table ).…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations